Implementasi Peraturan Pemerintah Bersama Tiga Menteri No.48/MEN.PP/XII/2008,PER.27/MEN/XII/2008 Tentang Peningkatan Pemberian Asi Selama Waktu Kerja di Tempat Kerja Dilakukan di Instusi Kesehatan di Kabupaten Garut - Tanti Suryawantie; Gin Gin Sugih Permana; Iwan Wahyudi (Jurnal Medika Cendikia, 2020)
Research has proven that lactation is the most optimum way to provide nutrients to babies for the early period of their lives (AIMI, 2012). The lactation corner is a space for breastfeeding or milking for employees or working mothers or mothers doing activities outside the home (leaving the baby at work, work facilities, and public places so that they can continue to give milk to their babies, either directly or through. The purpose of this research is to find out the implementation of goverment regulations three ministers about increasing breastfeeding during working time at the Health Institution in Garut, This research method uses qualitative methods with a phenomenological approach. The sampling used is purposive sampling with five informans and data collecting technique is in-depth interview. The results of this study obtained six themes, namely.: 1) Lack of knowledge related to government programs for breastfeeding for working mothers, 2) Not yet optimal policies for exclusive breastfeeding specifically for working mothers just for a general regulation, 3) Many health institutions as workplaces that do not yet have a special place for milking (lactation corner), 4) The leaders of institustion only provides implicit freedom to milking breastmilk, there are no written rules, 5). The experience of milking breast milk for working mothers is less pleasant because it is felt to be ineffective and privacy is disturbed, 6) Has protection rights for children and working mothers like of lactation corners and day care centers. Overall the rules of the government regulations has been carried out but it is still not optimal in its implementation. It is hoped that this research will be support to health institutions in the implementation of legislation with have a lactation corner as a place for lactation as well as a place for consultation about health and exchange of experiences in lactation and growing and developing of children